A Numerical Study on Mode II Fatigue Delamination Growth in Composite Laminates. Issue 1 (21st August 2022) - Russo, Angela; Sellitto, Andrea; Palumbo, Concetta; Riccio, Aniello
Abstract: In this paper, a numerical tool, able to mimic the delamination growth under cyclic loading conditions, has been adopted to investigate the mode II interlaminar damage growth in composite laminates. An improved Virtual Crack Closure Technique based model, mesh and time step independent, has been combined with a Paris‐Law equations‐based model to account for the effects of cycling loading conditions on the structural behavior of a specimen under an End‐Notched Flexure (ENF) test. The ANSYS FEM environment has been adopted for the numerical simulations and the numerical model has been implemented in ANSYS by adopting the Ansys Parametric Design Language (APDL). Comparisons at the coupon level with literature experimental data on unidirectional ENF samples have demonstrated the ability of the numerical model to simulate the Mode II fatigue delamination growth. Actually, useful indications on the damage propagation under fatigue loading condition have been provided by the proposed numerical model in conjunction with the experimental data taken from literature.